Ameliorating Effect of Klotho on Endoplasmic Reticulum Stress and Renal Fibrosis Induced by Unilateral Ureteral Obstruction (Iranian Journal of Kidney Diseases, 2015)
Introduction. Expression of Klotho is decreased and endoplasmic reticulum (ER) stress is activated in patients with chronic kidney disease. This study aimed to investigate the effect of Klotho protein on ER stress-related apoptosis and renal fibrosis in rates with unilateral ureteral obstruction (UUO). Materials and Methods. Twenty-four rats were divided into the sham, UUO, and Klotho treatment groups. Renal interstitial fibrosis model was induced by UUO in the rats of the latter two groups. Soluble Klotho protein was injected into the abdominal cavity. Serum and kidney samples were collected 14 days after the UUO surgery for examination of renal injury and renal interstitial fibrosis using hematoxylin-eosin and Masson trichrome staining methods. The level of apoptotic cells was assessed by the terminal deoxynucleotidyl transferase dUTP nick end labeling assay. Expression of 3 ER stress-related proteins including glucose-regulated protein 78, CCAAT/enhancer-binding protein homologous protein, and caspase-12 were measured. Results. Kidney dysfunction, increased renal injury index, and aggravated renal fibrosis were documented in the UUO group. Expression of Klotho in the UUO rats was remarkably decreased (P < .05) and expression of all three ER stress-related proteins were significantly upregulated, accompanied by increasing numbers of apoptotic cells (P < .05). Soluble Klotho administration improved kidney function, ameliorated pathological changes, decreased expressions of ER-stress related-proteins, and reduced the number of apoptotic cells. Conclusion. Unilateral ureteral obstruction decreased Klotho expression and activated ER stress and related apoptosis. Klotho administration ameliorated UUO-induced ER stress, inhibited apoptotic process, and attenuated renal fibrosis.